The Effect of Heroin Addiction on Human Sperm Parameters, Histone-to-Protamine Transition, and Serum Sexual Hormones Levels - Nazmara, Zohreh; Najafi, Mohammad; Rezaei-Mojaz, Samira; Movahedin, Mansoureh; Zandiyeh, Zahara; Shirinbayan, Peymaneh; Roshanpajouh, Mohsen; Asgari, Hamid Reza; Hosseini Jafari Lavasani, Leila; Koruji, Morteza (Urology Journal, 2019)
Purpose: To investigate the effects of heroin on sperm parameters, histone-to-protamine transition ratios in mature sperm, and serum reproductive hormone levels in active heroin users. Materials and Methods: Semen and blood samples were collected from 25 men who used only heroin for at least 12 months and the same number healthy men who did not use any drugs and did not suffer from infertility problems. Computer-based analysis, Aniline blue staining, and hormonal assessment were performed to provide valuable new information on the relationship between addiction and semen profile and serum reproductive hormone levels. Results: Our finding showed that semen pH (7.8 vs. 7.75), sperm motility (42.93 ± 3.89% vs. 68.9 ± 2.68%), and viability (73.27 ± 3.85% vs. 86.48 ± 1.05%), and sperm histone replacement abnormalities (32.33 ± 10.89% vs. 5.56 ± 0.85%) were significant differences in addicted group vs. non-exposed ones (P ? .05). In addition, serum sex hormone levels were not significantly differed between groups. There was a correlation between the amount of daily heroin consumption and LH level. We also observed that duration of drug dependence is correlated with sperm abnormalities. Conclusion: We concluded that heroin consumption affect sperm maturities such as histone-to-protamine ratio and impair semen profile in general and particularly sperm morphology and motility. Heroin may be considered as one of the idiopathic male infertility reason.